2013
DOI: 10.1093/gerona/glt153
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Changes in Leukocyte Telomere Length and Mortality in Humans

Abstract: This study establishes that certain lifestyle factors influence LTL dynamics. However, it questions the applicability of LTL dynamics as a predictor of mortality. We suggest cautiousness when assessing actual LTL attrition due to the need for high-quality DNA and the phenomena of regression to the mean.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
77
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(81 citation statements)
references
References 36 publications
3
77
0
1
Order By: Relevance
“…Most previous cross-sectional studies in which an association between smoking and short TL was reported were studies of female subjects only (11)(12)(13)(14)16), whereas those in which no association was reported were mostly studies of men or of older subjects (21,(23)(24)(25)(26), among whom estimates may be more likely to be biased because of higher rates of smoking cessation among older men with short TL. Previous longitudinal studies in which associations between smoking and TL attrition were reported involved younger subjects than did studies in which such an association was not reported (17)(18)(19)(20), further suggesting that estimates obtained from studies of older individuals could be biased because of adverse health-driven smoking cessation. In the Helsinki Businessmen Study, Strandberg et al (27) compared prospective and cross-sectional measures of smoking status and TL among men and reported findings consistent with those from our study.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Most previous cross-sectional studies in which an association between smoking and short TL was reported were studies of female subjects only (11)(12)(13)(14)16), whereas those in which no association was reported were mostly studies of men or of older subjects (21,(23)(24)(25)(26), among whom estimates may be more likely to be biased because of higher rates of smoking cessation among older men with short TL. Previous longitudinal studies in which associations between smoking and TL attrition were reported involved younger subjects than did studies in which such an association was not reported (17)(18)(19)(20), further suggesting that estimates obtained from studies of older individuals could be biased because of adverse health-driven smoking cessation. In the Helsinki Businessmen Study, Strandberg et al (27) compared prospective and cross-sectional measures of smoking status and TL among men and reported findings consistent with those from our study.…”
Section: Discussionmentioning
confidence: 96%
“…However, epidemiologic reports of smoking and TL have been inconsistent; in some studies, investigators reported shorter TL associated with smoking (11)(12)(13)(14)(15)(16)(17)(18)(19)(20), whereas others found no association (21)(22)(23)(24)(25)(26). This inconsistency has also been seen in studies of smoking and longitudinal measures of TL attrition, with associations between smoking and TL shortening seen in some studies (17,18) but not in others (19,20). Furthermore, a study of older men in Finland (27) found that smoking during midlife was associated with short TL measured later in life but that smoking was not associated with TL in crosssectional analyses conducted in later life, which suggests that the timing of smoking behavior assessment may be important.…”
mentioning
confidence: 99%
“…However, more recent studies investigating cancer-specific associations have also correlated longer LTL with increased risk of certain malignancies, including pancreatic cancer, hepatocellular carcinoma, melanoma, sarcoma and lung adenocarcinoma (19)(20)(21)(22)(23)(24). With regards to all-cause mortality, several recent prospective cohort studies could not establish an association between LTL and all-cause mortality (12,25,26), while the by far largest study comprising a cohort of nearly 65.000 Danish individuals found linear graded associations of LTL with all-cause, CVD and cancer mortality (27).…”
mentioning
confidence: 99%
“…Other recent meta-analyses support the concurrent associations between short telomeres and diabetes (8) and several cancers (9, 10). Several studies indicate that short telomeres from varied sources, including leukocytes and saliva, are related to early mortality (11-17), including a study with >60,000 adults (18), although null studies also exist (19)(20)(21)(22).Although these studies suggest that telomere length plays a role in disease, they are observational, and studies directly linking genetics of telomere length to disease would allow a more substantive inference of a causal role in disease pathogenesis. Recently, in humans, there were two such Mendelian randomization studies.…”
mentioning
confidence: 99%
“…Other recent meta-analyses support the concurrent associations between short telomeres and diabetes (8) and several cancers (9, 10). Several studies indicate that short telomeres from varied sources, including leukocytes and saliva, are related to early mortality (11-17), including a study with >60,000 adults (18), although null studies also exist (19)(20)(21)(22).…”
mentioning
confidence: 99%